Animality’s Problematic Place in Ortega’s Philosophy - Alonso, Marcos (2023)
This paper discusses a problem of great actuality in contemporary philosophy: the understanding of animal being and its relationship with human being. It analyses, specifically, the way in which this problem is addressed by the Spanish philosopher Ortega y Gasset, one of the first authors who deals with this issue as a specific and recurring theme in the context of his own thought. I show how Ortega arrives to this problem, which intellectual influences are behind his approach to the cluster of difficulties around the animal, and what place does this issue have in the context of Ortega’s general philosophical proposal. As a conclusion, I suggest that Ortega’s thought —as it is the case with many of the most relevant authors of the 20th Century— is marked by his considerations on animals; and that his ideas could still be fruitful when studying important problems concerning the status and the significance of the animal condition.